0730 Association Between Fruit Drink Intake and Healthy Sleep: An Examination of National Health Interview Survey data. (27th April 2018) - Chung, A; Seixas, A; Bademosi-Kalinowski, J; Williams, N; Robbins, R; Ogedegbe, O; Jean-Louis, G
Abstract: Introduction: Sugar-sweetened beverage (SSB) intake is associated with obesity, diabetes and metabolic syndrome risk. Harvard School of Public Health Beverage Guidelines ideally recommends zero intake of SSBs. SSBs include fruit drinks containing added sugar, and are often high calories, and low in nutritional value. Regular fruit drink intake may be an indicator of poor overall diet quality, which has been associated with sleep health. In this study, we assessed associations of fruit drink intake with healthy sleep. Methods: Data from the present analysis came from the National Health Interview Survey [2000–2016] (N=57, 252). The survey applies a stratified multistage sample survey of the resident civilian non-institutionalized US population. Respondents provided sociodemographic and physician-diagnosed chronic conditions. Self-reported sleep data was used to classify respondents based on sleep duration; insufficient sleepers were coded as (<7 hours/night) and long sleepers were coded as (>8hours /night, referenced to healthy sleepers (7–8 hours/night). Fruit drink frequency intake was classified as healthy (never or once monthly) compared to unhealthy fruit drink intake (daily or weekly). SPSS v 23 was used to conduct regression analysis to test our hypothesis. Results: The average age of the sample was 39.96 ± 2.47 years. Of the sample 48.3% were male and 51.7% were female. The race composition was as follows: 76.6% white and 23.4% comprised all other minority groups. Results of the adjusted logistic regression analysis showed that insufficient sleepers had a 5% greater likelihood of consuming fruit drinks (OR = 1.05, 95% CI 1.01–1.10, p<.05). Long sleepers were 30% more likely to consume fruit drinks (OR = 1.30 95% CI 1.20–1.40, p<0.001). Analysis adjusted for age, sex, race/ethnicity, and BMI. Conclusion: Long sleepers are more likely to be high fruit drink consumers. Fruit drink intake should be reduced as part of an overall diet regimen, which may also have implications for sleep health. Support (If Any): This research was supported by funding from the NIH (T32HL129953, RO1MD007716 and K07AG052685) and Dr. Williams was supported by NIH/NHLBI grant number K23HL125939.